2014
DOI: 10.1002/anie.201401125
|View full text |Cite
|
Sign up to set email alerts
|

Inside Cover: Asymmetric Catalysis on the Nanoscale: The Organocatalytic Approach to Helicenes (Angew. Chem. Int. Ed. 20/2014)

Abstract: The asymmetric synthesis of helicenes … … by a Fischer indolization catalyzed by a SPINOL-derived phosphoric acid is reported by B. List et al. in their Communication on page 5202 ff. The catalyst is designed for long-range control and bears extended p-surfaces at the 3,3'-position. It creates a chiral nanometer-sized pocket, which enables p-p stacking interactions between the substituents and the reactive intermediate. A variety of (di)azahelicenes were obtained with good to excellent yields and enentioselect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(36 citation statements)
references
References 0 publications
0
36
0
Order By: Relevance
“…Recent resurgence of interest in [ n ]­helicenes, ortho -annelated polycyclic aromatic molecules with nonplanar helical conjugation of the π-electron system, has revitalized the efforts to develop more efficient synthetic methods and expansive applications . [ n ]­Helicenes have become more accessible and modern synthetic methodologies have provided a variety of new [ n ]­heterohelicenes, in which the embedded heteroatom(s) could provide additional functionalities. , While these developments greatly facilitate the design and synthesis of open-shell [ n ]­helicene molecules, the detrimental reactivity of open-shell species remains the biggest impediment. The common, effective strategy for stabilizing open-shell species is to shield the radical site using bulky substituents, but it may be difficult to implement, as well as unappealing, in the design and synthesis of [ n ]­helicenes.…”
Section: Introductionmentioning
confidence: 99%
“…Recent resurgence of interest in [ n ]­helicenes, ortho -annelated polycyclic aromatic molecules with nonplanar helical conjugation of the π-electron system, has revitalized the efforts to develop more efficient synthetic methods and expansive applications . [ n ]­Helicenes have become more accessible and modern synthetic methodologies have provided a variety of new [ n ]­heterohelicenes, in which the embedded heteroatom(s) could provide additional functionalities. , While these developments greatly facilitate the design and synthesis of open-shell [ n ]­helicene molecules, the detrimental reactivity of open-shell species remains the biggest impediment. The common, effective strategy for stabilizing open-shell species is to shield the radical site using bulky substituents, but it may be difficult to implement, as well as unappealing, in the design and synthesis of [ n ]­helicenes.…”
Section: Introductionmentioning
confidence: 99%
“…Heterohelicenes with nitrogen as heteroatom, referred to as azahelicenes, can be of several types: pyridine-containing, pyridazine, pyrrole derivatives, etc. The pyrrole type is similar to the above molecules and has attracted some interest in recent years along with similar bis-azahelicene . A derivative of the former type aza[7]­helicene V has been synthesized and studied for its photophysical properties, and it also shows remarkably high thermal stability .…”
Section: Introductionmentioning
confidence: 99%
“…Previously, our research group reported the enantioselective synthesis of 1,1′-bitriphenylene-based carbo-, phospha-, and sila[7]­helicenes by the rhodium-catalyzed double [2+2+2] cycloaddition of a biphenyl-linked tetrayne with carbonyl-, phosphorus-, and silicon-linked diynes. In a similar way, the present [2+2+2] cycloaddition was applied to the enantioselective synthesis of benzopicene-based helical molecules (Scheme ). The reactions of binaphtyl-linked tetrayne 7 and carbonyl-lineked diynes 8a , b proceeded at room temperature in the presence of the cationic rhodium­(I)/( S )-H 8 –BINAP catalyst to give the corresponding benzopicene-based helical molecules 9a , b with high ee values, although the product yields were low.…”
Section: Results and Discussionmentioning
confidence: 97%